Mucormycosis Amid COVID-19 Crisis: Pathogenesis, Diagnosis, and Novel Treatment Strategies to Combat the Spread - Dogra, Shreya; Arora, Akanksha; Aggarwal, Aashni; Passi, Gautam; Sharma, Akanksha; Singh, Gurpal; Barnwal, Ravi P. (Frontiers in Microbiology, 2022)
The havoc unleashed by COVID-19 pandemic has paved way for secondary ominous fungal infections like Mucormycosis. It is caused by a class of opportunistic pathogens from Mucorales. Fatality rates due to this contagious infection are extremely high. Numerous clinical manifestations result in damage to multiple organs subject to the patient's underlying condition. Lack of a proper detection method and reliable treatment has made the management of this infection troublesome. Several reports studying the behavior pattern of Mucorales inside the host by modulation of its defense mechanisms have helped in understanding the pathogenesis of this angio-invasive infection. Many recent advances in diagnosis and treatment of this fungal infection have not been much beneficial. Therefore, there is a need to foster more viable strategies. This article summarizes current and imminent approaches that could aid effective management of these secondary infections in these times of global pandemic. It is foreseen that the development of newer antifungal drugs, antimicrobial peptides and nanotechnology-based approaches for drug delivery could help combat this infection and curb its spread.